Assessing the effectiveness of antimicrobial photodynamic therapy as an adjunct for pain reduction in herpes labialis: a comprehensive systematic review - Santana , Amanda Paino; Mulinari-Santos, Gabriel; Assunção, Wirley Gonçalves; Garcia, Valdir Gouveia; Theodoro, Letícia Helena (Journal of Oral Diagnosis, 2025)
Introduction: Herpes labialis, caused by the herpes simplex virus (HSV), leads to painful lesions around the lips. Current treatments primarily consist of topic antiviral agents, which often fail to provide immediate pain relief. Antimicrobial photodynamic therapy (aPDT) has emerged as a potential adjunctive treatment, but its effectiveness in reducing pain associated with herpes labialis remains unclear. Objective: This study aimed to evaluate the effectiveness of aPDT as an adjunctive treatment for reducing pain in herpes labialis. Methods: A systematic review was conducted following PRISMA guidelines and registered in the PROSPERO database (CRD42023474979). The review addressed the PICO question: Is aPDT effective in reducing pain compared to topic antiviral treatment alone? Electronic searches were conducted in PubMed/MEDLINE, Cochrane Library, and Web of Science for studies published until October 2024. Eligible studies were randomized controlled trials (RCTs) published in English that compared aPDT with antiviral agents. Results: Of the 184 articles identified, two studies involving 120 patients were selected for qualitative analysis. The findings indicated that aPDT, when used alongside topic antivirals, effectively reduced pain symptoms in herpes labialis compared to antiviral treatment alone. However, due to the limited number of studies and variability in outcome measures, the evidence remains preliminary. Conclusion: Based on this review, the use of aPDT as an adjunct to topical antiviral treatment appears to reduce pain symptoms associated with herpes labialis lesions compared to antiviral treatment alone. However, due to the limited number of randomized clinical trials and variability in the results, further research is necessary to establish standardized guidelines for its use.